Airfield and Highway Pavement 2013 2013
DOI: 10.1061/9780784413005.044
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tire Loading and Tire Pressure on Measured 3D Contact Stresses

Abstract: Three-dimensional (3D) tire-pavement contact stresses for two types of tires used by the truck industry (new generation wide-base tire [WBT] and dual-tire assembly [DTA]) were measured and compared. The testing matrix was composed of five loads () (26.6, 35.5, 44.4, 62.1, and 79.9 kN) and four tire inflation pressures () (552, 690, 758, and 862 kPa). The equipment used for measuring the 3D-contact stresses is described along with the testing procedure and the methodology followed during data processing. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…One of the key aspects of the considered truck tire loading is the three-dimensionality and nonuniformity of contact stresses. Not only was a database of experimentally measured contact loads and stresses generated, but actual tire-pavement contact loads and stresses were used as input to the finite element model (FEM) (14,15). Previous research has shown that the inclusion of lateral tangential contact stresses could lead to an increase of up to 47% in the surface tensile strain and a 5% increase in the tensile strain at the bottom of the AC (10).…”
Section: Finite Element Modelmentioning
confidence: 99%
“…One of the key aspects of the considered truck tire loading is the three-dimensionality and nonuniformity of contact stresses. Not only was a database of experimentally measured contact loads and stresses generated, but actual tire-pavement contact loads and stresses were used as input to the finite element model (FEM) (14,15). Previous research has shown that the inclusion of lateral tangential contact stresses could lead to an increase of up to 47% in the surface tensile strain and a 5% increase in the tensile strain at the bottom of the AC (10).…”
Section: Finite Element Modelmentioning
confidence: 99%
“…Analysis of the load-transfer mechanism of the tires considered in this research showed that the contact area of WBT is smaller (not to mention that there is a spacing between the tires of the dual assembly), although the contact length is longer for WBT. However, the maximum vertical contact stresses are similar for both tires for the specific loading case considered [17]. This indicates that the distribution of the applied load is more concentrated for WBT than for DTA, which translates into higher longitudinal and transverse tensile strains in the AC.…”
Section: Comparison Of Wbt and Dtamentioning
confidence: 71%
“…The FE method considers this true tirepavement contact loading. Details about tire contact measurements can be found elsewhere (24). Figures 2 and 3 are representative sketches for the measured contact areas of a WBT and a DTA, respectively.…”
Section: Loading Conditionsmentioning
confidence: 99%